Biocultural dimensions of endangered medicinal flora: Community knowledge, gender roles, and governance in the Pakistani Himalayas - Khanum, Rizwana; Noor, Ayesha; Hussain, Amir; Hussain, Rasheed; Akrum, Sardar; Qayum, Sidra; Ahmed Kazmi, Rizwan; Ali, Sardar Farhad; Khan, Shehryar; Hanif, Muhammad; Munir, Syed; ul Hassan, Sabih (Ethnobotany Research and Applications, 2026)
Background: The mountain communities of the Pakistani Himalayas possess rich ethnobotanical traditions centered around high-value medicinal plants such as Trillium govanianum Wall. ex D. Don, Dactylorhiza hatagirea (D. Don) Soo, Aconitum heterophyllum Wall. ex Royle, and Podophyllum hexandrum Royle. These species play vital roles in local health care, livelihoods, and cultural identity. Despite this significance, systematic documentation is limited, posing risks to both traditional ecological knowledge (TEK) and biodiversity conservation. Methods: From May 2024 to June 2025, an ethnobotanical survey was conducted across 24 mountain villages in Azad Jammu and Kashmir (Neelum, Leepa, and Hattian) and Khyber Pakhtunkhwa (Kaghan, Siran, and Galliat), at altitudes of 2,000–3,300 m. Using purposive and snowball sampling, A total of 120 respondents were engaged, including 98 household respondents and 22 key informants (10 forestry officers and 12 herbal traders) interviews were completed. Field observations and gender-segregated focus groups provided complementary insights into plant use, harvesting practices, and trade. Voucher specimens were authenticated at the Pakistan Museum of Natural History. Data were analyzed thematically for TEK, gender, and governance dynamics, alongside quantitative summaries of market dependence. Results: Community governance structures revealed extensive reliance on TEK for species identification, collection timing, and sustainable use. However, weak institutional enforcement and rising market demand threaten traditional management systems. Conclusions: Integrating indigenous knowledge and women’s participation into formal conservation and livelihood policies is essential for safeguarding both cultural resilience and Himalayan biodiversity. Keywords: Ethnobotany; Traditional Ecological Knowledge (TEK); Trillium govanianum; Dactylorhiza hatagirea; Aconitum heterophyllum; Podophyllum hexandrum; Gender roles; Community governance; Biocultural conservation; Pakistani Himalayas